Increase in invasive group A streptococcal infections in Milan, Italy: a genomic and clinical characterization - Mangioni, Davide; Fox, Valeria; Saltini, Paola; Lombardi, Andrea; Bussini, Linda; Carella, Francesco; Cariani, Lisa; Comelli, Agnese; Matinato, Caterina; Muscatello, Antonio; Teri, Antonio; Terranova, Leonardo; et al. (Frontiers in Microbiology, 2024)
Group A Streptococcus (GAS) causes multiple clinical manifestations, including invasive (iGAS) or even life-threatening (severe-iGAS) infections. After the drop in cases during COVID-19 pandemic, in 2022 a sharp increase of GAS was reported globally.GAS strains collected in 09/2022-03/2023 in two university hospitals in Milan, Italy were retrospectively analyzed. Clinical/epidemiological data were combined with whole-genome sequencing to: i) define resistome/virulome, ii) identify putative transmission chains, iii) explore associations between emm-types and clinical severity.Twenty-eight isolates were available, 19/28 (67.9%) from adults and 9/28 (32.1%) from pediatric population. The criteria for iGAS were met by 19/28 cases (67.9%), of which 11/19 (39.3%) met the further criteria for severe-iGAS. Pediatric cases were mainly non-invasive infections (8/9, 88.9%), adult cases were iGAS and severe-iGAS in 18/19 (94.7%) and 10/19 (52.6%), respectively.Thirteen emm-types were detected, the most prevalent being emm1.0 and emm12.0 (6/28 strains each, 21.4%). Single nucleotide polymorphism (SNP) analysis of emm1.0 and emm12.0 strains revealed pairwise SNP distance always >10, inconsistent with unique transmission chains.Emm12.0-type, found to almost exclusively carry virulence factors speH and spe-I, was mainly detected in children and in no-iGAS infections (55.6% vs. 5.3%, p=0.007 and 66.7% vs. 0.0%, p<0.001, respectively), while emm1.0-type was mainly detected in severe-iGAS (0.0% vs 45.5%, p=0.045).This study showed that multiple emm-types contributed to a 2022/2023 GAS infection increase in two hospitals in Milan, with no evidence of direct transmission chains. Specific emm-types could be associated with disease severity or invasiveness. Overall, these results support the integration of